IDENTIFIKASI RISIKO PADA PROYEK PENANGANAN LONGSORAN LERENG JALAN DI INDONESIA DENGAN METODE HOR (HOUSE OF RISK) - asep hilman rosadi; Indra Noer Hamdhan (Jurnal Jalan-Jembatan, 2022)
The implementation of the road slope landslide handling project, of course, there are many potential risks that occur. So that a risk management analysis is needed to anticipate the risks that occur. The purpose of this study was to identify risk events, risk factors and preventive measures in road slope landslide management projects in Indonesia. This research methodology uses questionnaires to experts in the field of road slope landslide handling projects in Indonesia with the House Of Risk (HOR) method and Delphi validation. There are 44 risk event variables, 36 risk factors and 24 preventive measures in this study. At the HOR phase 1 stage there are 22 priority risk factors from the original 36 risk factor variables. In HOR phase 2 and with the Pareto system, there are 13 priority precautions that need to be taken to prevent failures in handling road slope landslides. Through this research, preventive measures in anticipating risk factors in construction projects for handling road slope landslides in Indonesia are to tighten the qualifications of service providers during auctions, confirm contracted personnel have expertise and have internal supervision from the owner of service providers and supervisory consultants. Keywords:risk identification, risk factors, risk events, risk management, landslide.